PRESENTATION OF TOURIST DEMAND IN THE LIGHT OF LEGALITY, THE PHENOMENON AND THE PARADOX IN CONSUMPTION - Vujović, Slavoljub; Spajić, Jovan; Vukosavljević, Dejan (Economics of Agriculture, 2011)
The synthesis of various relevant theoretical concepts and empirical research confirms the dominance of ex-post approach to the study of organizational and developmental aspects of tourism. In this approach, as the main dominant spatial (geographic) or mechanisms of supply and demand (economic). The relationship between resources and needs suggests that all human efforts aimed at aligning the needs and opportunities. Tourist needs manifest themselves through the consumption of tourists, and quantify the amount of consumed-purchased. The dominance of commercial motive on the supply side economic approach gives primacy and economic interests. Without economics there is no life, and without resources there is no space economy, tourism. Physical access means, as the initial frame or basis always, a particular destination or tourist destination. Since the start of tourism to the present day, in the economy as a science, there is an uncompromising attitude that free time and free cash prerequisite of tourism development, and therefore represent the final objective of all economic activity. The mechanisms of the market, supply and demand or allow specific knowledge of developmental aspects of tourism. Disply of part travel demand through the economic laws, phenomena and paradoxes in consumption, can be seen that certain peculiarities conventional market mechanisms are not treated.